Low power consumption 4-channel variable optical attenuator array based on planar lightwave circuit technique - 任梅珍 张家顺 安俊明 王玥 王亮亮 李建光 吴远大 尹小杰 胡雄伟 (Chinese physics B, 2017)
The power consumption of a variable optical attenuator（VOA） array based on a silica planar lightwave circuit was investigated. The thermal field profile of the device was optimized using the finite-element analysis. The simulation results showed that the power consumption reduces as the depth of the heat-insulating grooves is deeper, the up-cladding is thinner,the down-cladding is thicker, and the width of the cladding ridge is narrower. The materials component and thickness of the electrodes were also optimized to guarantee the driving voltage under 5 V. The power consumption was successfully reduced to as low as 155 mW at an attenuation of 30 dB in the experiment.